Conhecimento dos profissionais e usuários da atenção básica sobre a doença pulmonar obstrutiva crônica - Queiroz, Maria Conceição de Castro Antonelli Monteiro de (2014)
Chronic respiratory diseases represent a major public health problem worldwide. Affect quality of life, physical disability and generating large socioeconomic impact. Often chronic obstructive pulmonary disease (COPD) is underdiagnosed. Delayed diagnosis may be related to inappropriate use of diagnoses and / or procedures lack of knowledge about the disease among health professionals and the general population. The aim of this study was to analyze the prevalence and factors associated with awareness of COPD among health professionals and primary care SUS users of a city of the Midwest factors. Methods: The study was analytical, observational, cross-sectional, conducted in basic health units, comprising the Health Centers (CS) and 26 Family Health Centers (CSF). Health professionals and users were interviewed using adapted with open and closed questions form. To assess knowledge of COPD among users of the units, we used an adapted structured form. 674 users, 95 doctors, 62 nurses and 30 managers in 12 CS and 26 CSF were interviewed between May 2013 and February 2014 Results: Of the 674 users interviewed, 84.3% reported knowing the term or the term COPD pulmonary emphysema; 9.2% reported knowing the term COPD. Dyspnea was the most frequent symptom attributed to COPD (70.6%). Regarding the main sources of knowledge about COPD, 43.1% of users reported the media and 36.4%, familiar with the disease. Among the 95 physicians interviewed, 28 (29.5%) had satisfactory knowledge about the diagnosis of COPD. Regarding the use of resources for the diagnosis of the disease (symptoms and spirometry), spirometry was mentioned by doctors (81.1%), then cited chest radiography (72.6%) and symptoms (51.6%) . Among the 62 nurses interviewed, 6.5% got the expected prevalence of COPD; 61.0% knew two risk factors (tobacco and wood); approximately 60.5% gave the expected response in relation to the recognition of two main associated diseases; 63.0% made the referral to the correct locations of spirometry. 30 managers, of which 48.3% had training in health were interviewed; all reported no units in its statistics on this disease; 13.0% and underestimated, overestimated the 54.8%, while 25.8% did not know what the expected response in relation to the reported prevalence of COPD; all identified tobacco, 64.5% and also wood smoke as risk factors for disease; 74.2% reported referral to the correct location for spirometry; 86.6% did not know what proportion of patients who had no access to treatment prescribed by the doctor. Conclusion: The prevalence of awareness of COPD is low among health professionals in primary care. The term COPD is unknown to most users, as opposed to the term emphysema. The prevalence of basic knowledge about the disease was lower among users. One of the sources of knowledge of COPD cited less frequently by users were physicians. The results of this study indicate possible causes of underdiagnosis of COPD in the population treated in primary care and may assist health managers to implement intervention projects that increase the rate of early diagnosis and treatment in COPD.